2018
DOI: 10.1590/s1980-6574201800020009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of deep-defending vs high-press on footballers’ tactical behaviour, physical and physiological performance: A pilot study

Abstract: The aim of this study was to explore the effects of a deep-defending vs high-press defending strategy on footballers' tactical behaviour, physical and physiological responses, when in numerical difference. Methods: Nineteen elite professional footballers (outfield players) participated in this study, playing an 11vs10 match (simulating an early dismissal) for two halves of 10 minutes on a full-sized regulation pitch. The 11-men team was instructed by the head coach to defend closer to goal in the first half (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…Consequently, this data implies that greater attacking success can be achieved by adopting a high-pressing defensive style (Low et al 2018). This supports the findings of Sarmento et al (2018) and Hughes and Lovell (2019) who both found a strong relationship between regaining the ball in attacking zones and positive attacking outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, this data implies that greater attacking success can be achieved by adopting a high-pressing defensive style (Low et al 2018). This supports the findings of Sarmento et al (2018) and Hughes and Lovell (2019) who both found a strong relationship between regaining the ball in attacking zones and positive attacking outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The most frequent locations of ball recovery in both the EPL and La Liga were the defence zone (EPL = 32.4%; La Liga = 31.8%) and pre-defence zone (La Liga = 32.4%; EPL = 30.6%), highlighting a preference towards recovering the ball closer to their own goal. This could be due to a compact, deep-defending style of defensive play before regaining possession, attempting to win the ball in deeper positions (Low et al 2018). These results are consistent with those highlighted by both Barreira et al (2014b) and Almeida et al (2014), where they both observed possession to be most frequently recovered in the pitch zones positioned closer to the goal that the team is defending.…”
Section: Discussionsupporting
confidence: 82%
“…4 ). Perhaps these results were due to the opponent team adopting a high defensive pressure strategy 30 which decreases the space available to create these passing opportunities. Consequently, the heatmaps display a high concentration of penetrative and support passing opportunities in a short area of the field (please see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recovering the ball closer to the opponent's goal increases the chance of scoring [26]. In addition, although the %KM indicator has not been part of any of the components, these teams could have a lower physical requirement associated with high-pressure defending [27]. It would be in a sense logical that the use of EA/HD would require playing in smaller spaces and therefore, the importance of %KM could be relativized.…”
Section: Discussionmentioning
confidence: 99%